Methodology (Engineering) - Rohaida, Che Man (Penerbit UMP, 2017)

(untitled)
Research methodology is a very important aspect of research. This module provides an overview and general steps involved in research methodology. There are three chapters in this modul e as shown i n Fi gure 1. 0; Research probl em ( Chapter 1), Research design (Chapter 2) and Research implementation (Chapter 3). Chapter 1 explains the techniques of defining a research problem and the construction of hypotheses and objectives. Chapter 2 presents the details of research design including the types of research methodology, identification of variables, materials, and instrument in the research process. Chapter 3 deals with the implementation of research. It provides the methods and types of data collection and the concept of validity and reliability. At the end, this module will provide the researcher the way to systematically solve the research problem.